(untitled) (Third Sector Social Economic Review, 2019)
In this study, household beef and veal demand was analyzed and time series of the period 1994-2018 was used. Before analyzing the study, stationarity problem encountered in multi-regression models where time series are used was analyzed using ADF and PP unit root tests. As a result of the analysis; it was determined that all variables in the demand function are first order stationary. The long-run correlation of the demand function which was determined to be integrated at the same level was evaluated under the framework of Johansen co-integration analysis. As a result of the co-integration analysis, it was determined that there was long-run correlation between the variables. However, the comment on the direction of the correlation and how long it will take to achieve the balance in the long term was obtained by Vector Error Correction Model (VEC) estimation result. As a result of the VEC Model estimation it was observed that error correction coefficient of veal and beef demand function was (0.137) between 0 and 1 and had a positive sign. This result expresses that long-run equilibrium from short-run disequilibrium is achieved at a rate of 13.7 %. Another result of the study is beef demand function coefficient of concordance. This coefficient was determine as (-0.13) and it shows that equilibrium is achieved in the long-run almost in 7.5 years. Therefore the result of the analysis expresses that the concordance rate of beef and veal demand to equilibrium is not so high.